Worry, intolerance of uncertainty, negative urgency, and their associations to paranoid thinking. (February 2022) - Zheng, Sally; Marcos, Michelle; Stewart, Kathleen E.; Szabo, Judit; Pawluk, Elizabeth; Girard, Todd A.; Koerner, Naomi
Abstract: Paranoia exists on a continuum with normal experience. Worry has been identified as a risk variable for paranoid thinking within non-clinical populations; however, studies have focused exclusively on the association between worry and persecutory beliefs, despite paranoia encompassing other domains (interpersonal sensitivities, mistrust, ideas of reference). Further, it is possible that worry-related processes account for more variance in paranoia than does the general tendency to worry. This study examined the associations of worry, intolerance of uncertainty (IU), and negative urgency (NU) to the four aforementioned domains of paranoia. N  = 311 undergraduate students completed self-report measures. Worry, IU, and NU were most strongly correlated with ideas of social reference and interpersonal sensitivities. Only IU and NU emerged as significant unique correlates of all domains of paranoid thinking when controlling for worry. Results suggest that the associations between worry and paranoia may be better explained by underlying processes, particularly IU. Future research should examine the association of other worry-related processes to paranoia, as well as the interactions between these processes and other diatheses (e.g., negative beliefs about self and others) in the generation of paranoia.